Dengue Incidence and Aedes Vector Collections in Relation to COVID-19 Population Mobility Restrictions - Surendran, S.N.; Nagulan, R.; Tharsan, A.; Kokila, S.; Ranjan, R. (Tropical Medicine And Infectious Disease Journal, 2022)
Contrary to expectation, dengue incidence decreased in many countries during the period when stringent population movement restrictions were imposed to combat COVID-19. Using a sea sonal autoregressive integrated moving average model, we previously reported a 74% reduction in the predicted number of dengue cases from March 2020 to April 2021 in the whole of Sri Lanka, with reductions occurring in all 25 districts in the country. The reduction in dengue incidence was ac companied by an 87% reduction in larval collections of Aedes vectors in the northern city of Jaffna. It was proposed that movement restrictions led to reduced human contact and blood feeding by Aedes vectors, accompanied by decreased oviposition and vector densities, which were responsible for diminished dengue transmission. These findings are extended in the present study by investi gating the relationship between dengue incidence, population movement restrictions, and vector larval collections between May 2021 and July 2022, when movement restrictions began to be lifted, with their complete removal in November 2021. The new findings further support our previous proposal that population movement restrictions imposed during the COVID-19 pandemic reduced dengue transmission primarily by influencing human–Aedes vector interaction dynamics.
Keywords: COVID-19; Dengue incidence; Dengue vectors; Dengue transmission; Mosquito vector–human interactions; Population movement restrictions; Jaffna; Sri Lanka